LEGAL FACTORS OF MARKETING ACTIVITIES: FOREIGN EXPERIENCE AND PROSPECTS FOR UKRAINE - KOVBAS, Ihor; KOVBAS, Galyna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
A fundamental approach to the study of theoretical issues and problem solving is the basis for the practical application of marketing activities in Ukraine. The article is devoted to the analysis of the principles of administrative and legal regulation of marketing activity, taking into account foreign experience. The author paid attention to the establishment and development of marketing schools as a basis for establishing marketing activities. It was found that American and European schools are characterized by a significant multilevel and effective combination of state control and self-regulation.Competition in Ukraine as an object of administrative and legal support has been studied. The measures of an administrative nature, which are taken by the relevant entities for the proper implementation of the administrative and legal protection of competition in the European Union, are highlighted. An attempt is made to characterize marketing information, the main legal acts in this area and problematic issues requiring legislative regulation are considered. The work examines certain issues of the theoretical, methodological and legal foundations of information relations in the field of advertising services. The main trends of the legislative regulation of advertising activity in the countries of the European Union are analyzed. Attention is paid to the system of consumer rights protection, in particular attention is paid to the global practice of activity in this field of legal relations. It was established that the adaptation of the national legislation regulating relations in the field of marketing activities should be carried out taking into account modern conditions and requests of the marketing industry. The evaluation of the activities of the bodies included in the system of state regulation of the marketing industry was carried out.The analysis of regulatory and legal support of marketing activity in Ukraine made it possible to establish that the main problems of the legislative framework are related to the imperfection of the conceptual and terminological apparatus, the insufficiently clear definition of the administrative and legal influence on entities that carry out marketing activities, the fragmentation of the powers of controlling bodies, the absence of legislative the basis for the development of the self-regulation system. On the basis of the researched materials, conclusions were formulated regarding the improvement of administrative and legal regulation of marketing activity in the direction of harmonization with European legislation and the expansion of many important interpretations and provisions.
Keywords: marketing activity; administrative and legal regulation; marketing communications; competition; consumer rights protection